Experimental desktop 3D printing using dual extrusion and water-soluble polyvinyl alcohol. Issue 5 (17th August 2015) - Eujin Pei, Dr; Duran, Chelsea; Subbian, Vignesh; Giovanetti, Matthew T.; Simkins, Jeffrey R.; Beyette Jr, Fred R.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to discuss the use of polyvinyl alcohol (PVA) as a water-soluble support material in desktop three-dimensional (3D) printing. Using a water-soluble material as one of the printing filaments in a dual-extrusion 3D printer provides the flexibility of printing support structures and rafts in complex components and prototypes. This paper focuses on the challenges of acrylonitrile butadiene styrene (ABS)–PVA dual-extrusion printing, and optimal settings and techniques for such hybrid printing. Design/methodology/approach – Several hybrid ABS–PVA parts were printed using a commercial desktop 3D printer. An experimental study was designed to examine the solubility of the PVA support in water by varying four different parameters: length of time in water, water temperature, stirring rate and PVA surface area. The rate of PVA solubility in water was then used to examine its relationship with each parameter. Findings – Numerous problems were encountered while printing ABS–PVA printing parts, including storing the spool of PVA in a dry environment, determining optimal extrusion and build plate temperatures and ABS–PVA adherence during dual extrusion printing. There is no strong literature to address these challenges. Hence, optimal settings and techniques for effective hybrid ABS–PVA were determined. Print yields were also recorded to examine the reliability of ABS–PVA printing. Research limitations/implications – The tendency of PVA to absorb moisture resulted in a number of build fails and prevented build times longer than 40 minutes. Future work can explore how to print PVA directly from a dry environment. Practical implications – The optimal settings and techniques for dual-extrusion ABS–PVA printing that are presented in this paper can effectively be used to explore prototyping of geometrically complex parts with PVA as support material. Originality/value – In addition to the practical implications, the results from this work are a valuable addition to the literature related to printing using water-soluble polymers such as PVA. The experimental methods and techniques of this paper can be used to assess the reliability of similar 3D printing technologies.